2014
DOI: 10.1177/1090820x14536726
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Injuries in Aesthetic Breast Surgery: Systematic Review and Treatment Options

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…In a study by von Sperling, investigators found that three-quarters of the patients experienced some sensory changes, with hypoesthesia as the most common neuropathic symptom in these patients [11]. In a larger systematic review of nerve injuries in breast augmentation by Ducic et al, investigators found that 13.57-15.44% of breast augmentation patients experienced some sensory changes, and around 9% of those patients experienced hypoesthesia [19]. Pain and hyperesthesia were the next most common neuropathic symptoms reported [19].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…In a study by von Sperling, investigators found that three-quarters of the patients experienced some sensory changes, with hypoesthesia as the most common neuropathic symptom in these patients [11]. In a larger systematic review of nerve injuries in breast augmentation by Ducic et al, investigators found that 13.57-15.44% of breast augmentation patients experienced some sensory changes, and around 9% of those patients experienced hypoesthesia [19]. Pain and hyperesthesia were the next most common neuropathic symptoms reported [19].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Commonly reported symptomology by patients include sensations of pins and needles, burning, and numbness [11]. In addition, patients may experience itching, tingling, or tenderness in surgical sites from nerve disruption or damage [11,19,20]. Dysesthesia, hypoesthesia, or hyperesthesia are also experienced by patients following breast surgery [19].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 3 more Smart Citations